(untitled) (Research, Society and Development, 2021)
From the perspective of reflecting on the environmental conception of elementary school teachers II who work in various areas of knowledge, we present for the debate the conceptions of Critical Environmental Education and Conservative Environmental Education, focusing on the answers of teachers to the following question: "How do you define Environmental Education?" The objective was to analyze from the teachers’ answers the conceptions regarding Environmental Education for an awareness of social and environmental issues and how they interfere in their pedagogical practice. A qualitative research was carried out, in which the empirical material was produced from the answers to a questionnaire submitted to teachers of various levels and areas of knowledge. The results indicate that many of the interviewees emphasize the environment as nature, the place where one lives and where resources are extracted. Another portion of the interviewees thinks about Environmental Education in a critical way, because they perceive it as fundamental, in the search for dialogue between action-reflection-action around daily experiences. On the other hand, a smaller portion of teachers could not define Environmental Education, showing that there is no real knowledge about it, which may be a consequence of a deficiency in initial and continuing education. This result points to the need for a change in the way environmental education is treated in teacher education.